Conjunctivitis as a common adverse effect of dupilumab in atopic dermatitis - Mikołaj Cichoń; Jowita Sroka-Tomaszewska; Magdalena Trzeciak (Termedia Publishing House, 2023)
Dupilumab is a monoclonal antibody against the a subunit of the receptor for interleukin 4 and interleukin 13. It is the first biological drug registered in the world for the treatment of atopic dermatitis. Dupilumab turned out to be a milestone in the treatment of atopic dermatitis and an alternative to standard immunosuppressive drugs. In numerous multicenter studies, including real-life studies, it has been proven that dupilumab brings a significant improvement in subjective and objective clinical symptoms in atopic dermatitis. Conjunctivitis is one of the side effects of dupilumab treatment. It is estimated that it affects about 14% of patients with atopic dermatitis. The mechanisms leading to it are not yet fully understood.